Epidemiological Features of Sinonasal Adenocarcinoma and Prognostic Nomogram: A Study Based on the SEER Database - Lu Yang MMed; Yufeng Gu MMed; Lei Yu MMed; Qiang Zhou MMed; Li Liu MMed; Ying Mao MMed; Ji Ma MMed; Yong Li PhD; Na Li PhD (Cancer Control)
Objective Our study aimed to update demographic profiles of sinonasal adenocarcinoma (SNAC) between 2000 and 2020, identify independent prognostic risk factors, and devise a predictive nomogram for overall survival (OS). Methods Utilizing the Surveillance, Epidemiology, and End Results (SEER) database, cases of SNAC from 2000 to 2020 were analyzed for incidence trends. Univariate and multivariate Cox regression models helped pinpoint factors impacting patient survival. A prognostic nomogram was then created based on these factors and assessed via concordance index, ROC analysis, and calibration curves. Results Analysis of 488 SNAC patients indicated a rising incidence, peaking among 60-69-year-olds, with a male predominance and the highest occurrence in White populations. Common sites of occurrence included the nasal cavity, and the maxillary and ethmoid sinuses. The nomogram, developed with 184 patients, highlighted older age (≥70), male sex, advanced T stages (T4b, T4a), distant metastasis, larger tumors (≥5 cm), and lack of surgery as poor prognostic indicators. Nomogram performance demonstrated strong predictive capabilities in both training and validation cohorts. Conclusion This investigation, leveraging the SEER database, elucidates the epidemiology of SNAC and pinpoints key adverse prognostic determinants: age ≥70, male gender, T stages T4b and T4a, presence of distant metastasis, tumor size exceeding 5 cm, and absence of surgical intervention. Moreover, it introduces a novel nomogram capable of accurately forecasting 1-, 3-, and 5-year OS for SNAC patients, thereby enhancing disease comprehension and facilitating the formulation of tailored therapeutic strategies by clinicians.